Homocysteine Levels in Parkinson's Disease: Is Entacapone Effective?. (17th July 2016) - Kocer, Bilge; Guven, Hayat; Comoglu, Selim Selcuk
Abstract : Plasma homocysteine (Hcy) levels may increase in levodopa-treated patients with Parkinson's disease (PD) as a consequence of levodopa methylation via catechol-O-methyltransferase (COMT). Results from previous studies that assessed the effect of COMT inhibitors on levodopa-induced hyperhomocysteinemia are conflicting. We aimed to evaluate the effects of levodopa and entacapone on plasma Hcy levels. A hundred PD patients were enrolled to the study and divided into three treatment groups (group I: levodopa and/or dopamine agonists; group II: levodopa, entacapone, and/or a dopamine agonist; and group III: dopamine agonist alone). We measured the serum B12, folic acid, and Hcy levels in all patients. There were no statistically significant differences between groups in terms of modified Hoehn and Yahr stages, Unified Parkinson's Disease Rating Scale II/III, Standardized Mini-Mental Test scores, and serum vitamin B12 and folic acid levels. Plasma median Hcy levels were found above the normal laboratory values in groups I and II, but they were normal in group III. However, there was no statistically significant difference in plasma Hcy levels between groups. Our results showed that levodopa treatment may cause a slight increase in the Hcy levels in PD compared with dopamine agonists and that COMT inhibitors may not have a significant effect on preventing hyperhomocysteinemia.